The Role of Digital Marketing and Product Quality on Consumer Buying Interest in Online Stores - Kasmad Kasmad (International Journal of Artificial Intelligence Research, 2022)
The purpose of this study is to analyze the influence of Digital Marketing on consumer buying interest in the Online Store and analyze the effect of product quality on consumer buying interest in the Online Store. This research is an associative quantitative research which is used to determine the effect of digital marketing and product quality on consumer buying interest. The research chose an online store in Jakarta as the research location. Respondents as many as 280 online store consumers who were selected by accidental sampling or the sample was chosen by chance at the location and was considered suitable as a data source. The online questionnaire is distributed through social media and in the questionnaire there will be five score options for each statement that can be chosen according to the actual situation felt by the respondent. The data will be processed and used to test the hypotheses that have been proposed using structural equation modeling analysis with the SmartPLS 4.0 software data processing tool. The conclusions of this study are (1) digital marketing has a positive and partially significant effect on online store consumer buying interest, (2) product quality partially positive and significant effect on online store consumer buying interest, and (3) digital marketing and product quality simultaneous positive and significant effect on online store consumer buying interest